FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DAN ALUMNI PRODI MHU MENJADI PENGUSAHA TOUR AND TRAVEL(Studi Kasus : Program Studi Manajemen Haji Dan Umrah UIN Sjech M. Djamil Djambek Bukittinggi ) - Riska Zakia; Rusydi Fauzan (BORJUIS: JURNAL OF ECONOMY, 2023)
The purpose of this study was to determine what factors influence the interest of students and alumni of the MHU study programto become tour and travel entrepreneurs. The data used are second and first level data. There were 76 respondents surveyed using the Slovin formula. The method of collection and using observation tools in the form of stationery to collect information and survey tools such as Likert scales for scientific inquiry. Variable factor analysis was the method used in the data analysis technique. The findings of this study indicate that the factors that influence the interest of students and alumni of the MHU study program to become tour and travel entrepreneurs class of 2017, 2018, 2019 and 2020 consisting of 310 students and alumni consist of 20 variables which are grouped into 6 factors, namely: the first factor is external and internal, the second factor is self- efficacy, the third factor is capital income, the fourth factor is entrepreneurship education, the fifth factor is motivation.